A method for pyrolyzing and recovering glass fiber from retired fan blades and the resulting regenerated glass fiber

By using an inert atmosphere and specific pyrolytic dehydrants in the pyrolytic reaction of the decommissioned fan blades, the problem of pyrolytic carbon removal is solved, and efficient recycling and cleaning of glass fibers is achieved, avoiding damage to the fiber performance by the post-treatment process.

CN115739929BActive Publication Date: 2025-03-18NORTH CHINA ELECTRIC POWER UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211437839.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-16
Publication Date
2025-03-18
Estimated Expiration
2042-11-16

AI Technical Summary

Technical Problem

In the prior art, when the pyrolysis and recovery of glass fibers with the blades of the retired fan are difficult to effectively remove the pyrolysis carbon, resulting in the inability to effectively bond with the resin, the process is complicated and unfavorable to the fiber performance.

Method used

The pyrolysis reaction is carried out under an inert atmosphere, and a specific pyrolysis agent, such as acetic acid, hydrogen peroxide, organic alcohol and persulfate aqueous solution is added at high temperature to generate active free radicals with strong oxidation capacity, promote the complete cracking of the resin matrix and remove the pyrolysis carbon.

Benefits of technology

Without adding the post-treatment process, glass fibers with clean surfaces and good mechanical properties are directly obtained, with a carbon content of <1%, and a tensile strength retention rate of more than 97%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115739929B_ABST
    Figure CN115739929B_ABST
Patent Text Reader

Abstract

The present invention provides a method for pyrolyzing and recovering glass fiber from retired fan blades and the obtained regenerated glass fiber. The method for pyrolyzing and recovering glass fiber from retired fan blades comprises: (1) removing metal components from retired fan blades and cutting them into blade blocks; (2) placing the blade blocks and a pyrolysis promoter in a pyrolysis reactor to carry out pyrolysis reaction under an inert atmosphere; wherein the pyrolysis promoter is selected from at least one of acetic acid, hydrogen peroxide, organic alcohol, and persulfate; (3) after the reaction, taking out the solid product from the pyrolysis reactor, cooling it, and obtaining regenerated glass fiber. The present invention optimizes and improves the pyrolysis reaction, avoids the influence of pyrolysis carbon after resin pyrolysis on the quality of glass fiber, realizes the reduction, harmlessness, and resource utilization of retired fan blades with simple steps and low energy consumption, and the recovered glass fiber is clean and has good performance, and has both environmental protection and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of resource recovery, and in particular to a method for recovering glass fibers by pyrolysis of retired wind turbine blades and the regenerated glass fibers obtained. Background Art

[0002] With the rapid development of the wind power industry, the annual new installed capacity of wind power has increased significantly. Wind turbine blades are an important part of wind turbines. The surge in wind power installed capacity will inevitably lead to a large number of retired blades. At present, the design life of wind turbine blades is usually 20 years. The early operating blades on the market have been more than 15 years old. Therefore, some blades put into operation in old wind farms have begun to be retired one after another. In the future, the total number of retired blades will increase rapidly.

[0003] Glass fiber composite materials are currently the most widely used high-performance composite materials in wind turbine blades due to their low price and excellent comprehensive performance. Fiber and resin in wind turbine blades account for more than 90% of the total mass of the blades. Traditional landfill treatment occupies a large amount of land, which is likely to pollute the soil and groundwater, and it is even more difficult to achieve resource recovery of high-value fibers. Direct incineration of retired wind turbine blades will also produce toxic substances such as dioxins, which seriously pollute the environment and endanger human health.

[0004] Pyrolysis technology has the advantages of significant reduction, complete harmlessness, and high degree of resource utilization. It is an important type of composite material recycling technology. Chinese patent CN113046107A discloses a pyrolysis recovery system, which combines a pyrolysis reactor and a circulating fluidized bed boiler to recycle and dispose of retired fan blades; Chinese patent CN114656985A discloses high-temperature pyrolysis of retired fan blades in high-temperature nitrogen, and then wind separation to obtain fiber materials; Chinese patent CN112024583A discloses thermal cracking of retired fan blades in a fixed bed gasifier, and then recovering glass fibers from the generated ash; Chinese patent CN113278438A discloses using low-grade steam from coal-fired power plants as an isolation gas in the reaction process, and using microwave pyrolysis to recover fibers from retired fan blades. However, the thermal decomposition of polymer resins in retired wind turbine blades will produce pyrolytic carbon and remain in these solid products. Therefore, the solid products obtained by the above pyrolysis are not clean regenerated glass fibers, and the carbon-containing regenerated fibers usually cannot be effectively bonded with the resin and are difficult to reuse. In order to remove these residual carbons, the above technical solutions all need to add post-processing processes such as mechanical separation or oxidation, which makes the recycling process more complicated, increases the energy consumption of the system, and also has an adverse effect on the performance of the regenerated fibers. At present, there is no mature and effective technology to solve these problems.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for pyrolyzing and recovering glass fibers from retired wind turbine blades, which method can directly obtain glass fibers with clean surfaces and good mechanical properties without the need for further post-processing processes such as mechanical separation or oxidation to remove pyrolytic carbon.

[0007] A second object of the present invention is to provide a regenerated glass fiber obtained by the above method.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] In a first aspect, the present invention provides a method for pyrolyzing and recovering glass fibers from retired wind turbine blades, comprising the following steps:

[0010] (1) After removing the metal components from the retired wind turbine blades, cut them into blade blocks;

[0011] (2) placing the leaf block obtained in step (1) and a pyrolysis-promoting agent in a pyrolysis reactor to carry out a pyrolysis reaction under an inert atmosphere; wherein the pyrolysis-promoting agent is selected from an aqueous solution prepared from one of acetic acid, hydrogen peroxide, an organic alcohol (aliphatic monohydric or dihydric alcohol), and a persulfate;

[0012] (3) After the reaction, the solid product is taken out from the pyrolysis reactor and cooled to obtain regenerated glass fiber; the carbon content of the regenerated glass fiber is less than 1%, and the tensile strength retention rate of the regenerated glass fiber is above 97%.

[0013] Each step is described in detail below.

[0014] Step (1)

[0015] First, the metal components of the retired wind turbine blades are removed and then mechanically cut into blade blocks of appropriate sizes.

[0016] Preferably, the size of the blade block is 30-100 cm×20-50 cm×10-20 cm.

[0017] Step (2)

[0018] Then, the blade block is placed in a pyrolysis reactor and a pyrolysis reaction is carried out under an inert atmosphere and at a certain temperature. During the pyrolysis, a certain amount of aqueous solution prepared by acetic acid, hydrogen peroxide, organic alcohol (for example, one of aliphatic monohydric or dihydric alcohols such as isopropanol, n-butanol, ethylene glycol, etc.), persulfate (for example, one of sodium persulfate, potassium persulfate, potassium hydrogen persulfate), etc. is introduced into the reactor as a pyrolysis promoter.

[0019] Preferably, the inert atmosphere for the pyrolysis reaction is a nitrogen or argon atmosphere.

[0020] Preferably, the temperature of the pyrolysis reaction is 400-600° C.; the time of the pyrolysis reaction is 30-60 min.

[0021] Preferably, the concentration of the pyrolysis-promoting agent is 5 to 10 mol / L, and the ratio of its usage to the mass of the leaf block is 1 to 1.5 L / kg.

[0022] The present invention adopts a special type of pyrolysis promoting agent, which has the common feature of being able to generate active free radicals with strong oxidizing ability at high temperature, such as H· free radicals, OH· free radicals, SO4 - Free radicals, etc. These active free radicals collide effectively with the polymer macromolecular chains, so that the resin matrix can fully combine with the free radicals to form short-chain small molecular products during the cracking process, inhibit the secondary polymerization of the polymer cracking products and the formation of pyrolytic carbon, and promote the complete cracking of the resin matrix (epoxy resin) in the retired fan blades, thereby achieving the in-situ removal of the organic pyrolytic carbon remaining on the fiber surface after the cracking of the organic resin under a reducing atmosphere, avoiding the damage to the performance of the regenerated glass fiber caused by post-treatment carbon removal processes such as combustion and mechanical separation.

[0023] Step (3)

[0024] The solid product after the reaction is taken out from the pyrolysis reactor and cooled to obtain regenerated glass fiber with a clean surface and good mechanical properties.

[0025] The carbon content of the regenerated glass fiber is less than 1%, and the tensile strength retention rate of the regenerated glass fiber can reach more than 97%.

[0026] In a second aspect, the present invention provides a regenerated glass fiber obtained by the above method;

[0027] The carbon content of the regenerated glass fiber is less than 1%, and the tensile strength retention rate of the regenerated glass fiber can reach more than 97%.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention uses rapid pyrolysis technology to treat retired fan blades, avoiding the waste of resources caused by landfill treatment and the generation of toxic and harmful gases such as dioxins by direct incineration; at the same time, the pyrolysis reaction is optimized and improved to avoid the influence of pyrolysis carbon oxidation after resin pyrolysis on the quality of glass fiber. During the pyrolysis process, a pyrolysis-promoting agent is added to the reactor to release H·, OH·, SO4 at high temperature. -·Active free radicals with strong oxidizing ability can effectively collide with polymer macromolecular chains, so that the resin matrix can fully combine with free radicals to form short-chain small molecular products during the cracking process, inhibit the secondary polymerization of polymer cracking products and the formation of pyrolytic carbon, and promote the complete cracking of the resin matrix (epoxy resin) in the retired fan blades, thereby achieving the in-situ removal of organic pyrolytic carbon remaining on the fiber surface after cracking of organic resin under reducing atmosphere. It is possible to successfully recover glass fibers with clean surfaces and good performance without adding any post-processing processes, avoiding the damage to fiber performance and the increase in system energy consumption caused by post-processing processes such as combustion and mechanical separation. Regenerated glass fibers can produce good interface adhesion with other polymer resins, thereby producing new composite materials.

[0030] 2. The method proposed in the present invention can effectively achieve the reduction, harmlessness and resource utilization of retired wind turbine blades, and at the same time can recycle clean and high-value recycled glass fibers. The process is simple, energy-saving and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic structural diagram of a pyrolysis reactor according to an embodiment of the present invention;

[0032] Figure 2 A cross-sectional view of a pyrolysis reactor according to an embodiment of the present invention.

[0033] Icons: 1-inner chamber of pyrolysis reactor; 2-outer chamber of pyrolysis reactor; 3-inert gas and pyrolysis promoter inlet channel; 4-pyrolysis gas outlet channel; 5-high-temperature flue gas inlet channel; 6-low-temperature flue gas outlet channel. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0036] The carbon content and tensile strength retention rate of recycled glass fiber are used as recycling effect evaluation indicators, and the calculation formula is:

[0037]

[0038]

[0039] In formula (1): R is the carbon content of the regenerated glass fiber, %; m c is the mass of residual pyrolytic carbon on the surface of regenerated glass fiber, kg; m is the mass of regenerated glass fiber, kg.

[0040] In formula (2), X is the tensile strength retention rate of the regenerated glass fiber, %; σ is the tensile strength of the regenerated glass fiber, MPa; σ0 is the tensile strength of the original glass fiber, MPa.

[0041] The pyrolysis reaction of the embodiment can be carried out in a pyrolysis reactor, the structure of which is as follows: Figure 1 , Figure 2 As shown, but not limited to this; the specific process is: placing the leaf block in the inner chamber 1 of the pyrolysis reactor and performing a pyrolysis reaction at high temperature; during the pyrolysis process, an inert gas and a certain amount of pyrolysis promoter are continuously introduced into the inner chamber 1 of the pyrolysis reactor through the inert gas and pyrolysis promoter inlet channel 3; the high calorific value combustible gas produced by pyrolysis is discharged and burned through the pyrolysis gas outlet channel 4, and the high-temperature flue gas produced by the combustion is introduced into the outer chamber 2 of the pyrolysis reactor through the high-temperature flue gas inlet channel 5 for heat exchange to provide energy for the pyrolysis process. After heat exchange, the flue gas is discharged through the low-temperature flue gas outlet channel 6; after the reaction time is reached, the solid product produced by the reaction is taken out from the inner chamber 1 of the pyrolysis reactor and cooled.

[0042] Example 1

[0043] First, the retired fan blades are mechanically cut into 30cm×30cm×10cm blade blocks; the pyrolysis reactor is heated to 550°C and purged with nitrogen; then the cut blade blocks are quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; nitrogen is continuously introduced during the pyrolysis process, and a 6mol / L acetic acid aqueous solution is introduced into the reactor at a mass ratio of 1.5L / kg to the blade block; after 60 minutes of reaction, the solid product produced by the reaction is taken out of the reactor, and after cooling, a glass fiber with a clean surface and a carbon content of 0.9% is obtained. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this embodiment is 97.6% of the original fiber.

[0044] Example 2

[0045] First, the retired fan blades are mechanically cut into 50cm×20cm×10cm blade blocks; the pyrolysis reactor is heated to 600°C and purged with argon; then the cut blade blocks are quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; during the pyrolysis process, argon is continuously introduced, and a 10mol / L acetic acid aqueous solution is introduced into the reactor at a mass ratio of 1L / kg to the blade block; after 40 minutes of reaction, the solid product produced by the reaction is taken out of the reactor, and after cooling, a glass fiber with a clean surface and a carbon content of 0.8% is obtained. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this embodiment is 98.5% of the original fiber.

[0046] Example 3

[0047] First, the retired fan blades are mechanically cut into 50cm×40cm×10cm blade blocks; the pyrolysis reactor is heated to 400°C and purged with nitrogen; then the cut blade blocks are quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; nitrogen is continuously introduced during the pyrolysis process, and a 5mol / L hydrogen peroxide aqueous solution is introduced into the reactor at a mass ratio of 1.5L / kg to the blade block; after 50 minutes of reaction, the solid product produced by the reaction is taken out of the reactor, and after cooling, a glass fiber with a clean surface and a carbon content of 0.8% is obtained. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this embodiment is 98.2% of the original fiber.

[0048] Example 4

[0049] First, the retired fan blades are mechanically cut into 70cm×30cm×10cm blade blocks; the pyrolysis reactor is heated to 450°C and purged with argon; then the cut blade blocks are quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; during the pyrolysis process, argon is continuously introduced, and an 8mol / L hydrogen peroxide aqueous solution is introduced into the reactor at a mass ratio of 1L / kg to the blade block; after 50 minutes of reaction, the solid product produced by the reaction is taken out of the reactor, and after cooling, a glass fiber with a clean surface and a carbon content of 0.6% is obtained. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this embodiment is 97.1% of the original fiber.

[0050] Example 5

[0051] First, the retired fan blades are mechanically cut into 30cm×20cm×20cm blade blocks; the pyrolysis reactor is heated to 500°C and purged with nitrogen; then the cut blade blocks are quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; nitrogen is continuously introduced during the pyrolysis process, and a 7mol / L isopropanol aqueous solution is introduced into the reactor at a mass ratio of 1.5L / kg to the blade block; after 40 minutes of reaction, the solid product produced by the reaction is taken out of the reactor, and after cooling, a glass fiber with a clean surface and a carbon content of 0.8% is obtained. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this embodiment is 99.4% of the original fiber.

[0052] Example 6

[0053] First, the retired fan blades are mechanically cut into 70cm×20cm×10cm blade blocks; the pyrolysis reactor is heated to 550°C and purged with argon; then the cut blade blocks are quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; during the pyrolysis process, argon is continuously introduced, and a 6mol / L n-butanol aqueous solution is introduced into the reactor at the same time, and the mass ratio of the amount to the blade block is 1.5L / kg; after 30 minutes of reaction, the solid product produced by the reaction is taken out of the reactor, and after cooling, a glass fiber with a clean surface and a carbon content of 0.9% is obtained. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this embodiment is 98.3% of the original fiber.

[0054] Example 7

[0055] First, the retired fan blades are mechanically cut into blade blocks of 50cm×30cm×10cm; the pyrolysis reactor is heated to 500°C and purged with nitrogen; then the cut blade blocks are quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; nitrogen is continuously introduced during the pyrolysis process, and a 5mol / L ethylene glycol aqueous solution is introduced into the reactor at a mass ratio of 1L / kg to the blade block; after 50 minutes of reaction, the solid product produced by the reaction is taken out of the reactor, and after cooling, a glass fiber with a clean surface and a carbon content of 0.6% is obtained. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this embodiment is 98.0% of the original fiber.

[0056] Example 8

[0057] First, the retired fan blades are mechanically cut into 50cm×30cm×20cm blade blocks; the pyrolysis reactor is heated to 550℃ and purged with argon; then the cut blade blocks are quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; during the pyrolysis process, argon is continuously introduced, and a 9mol / L sodium persulfate aqueous solution is introduced into the reactor at the same time, and the mass ratio of the amount to the blade block is 1.5mol / L; after 40 minutes of reaction, the solid product produced by the reaction is taken out of the reactor, and after cooling, a glass fiber with a clean surface and a carbon content of 0.7% is obtained. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this embodiment is 97.9% of the original fiber.

[0058] Example 9

[0059] First, the retired fan blades are mechanically cut into 100cm×20cm×20cm blade blocks; the pyrolysis reactor is heated to 450°C and purged with nitrogen; then the cut blade blocks are quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; nitrogen is continuously introduced during the pyrolysis process, and a 6mol / L potassium persulfate aqueous solution is introduced into the reactor at the same time, and the mass ratio of the amount to the blade block is 1.3L / kg; after 60 minutes of reaction, the solid product produced by the reaction is taken out of the reactor, and after cooling, a glass fiber with a clean surface and a carbon content of 0.6% is obtained. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this embodiment is 98.7% of the original fiber.

[0060] Example 10

[0061] First, the retired fan blades are mechanically cut into 50cm×50cm×20cm blade blocks; the pyrolysis reactor is heated to 500°C and purged with argon; then the cut blade blocks are quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; during the pyrolysis process, argon is continuously introduced, and 8 mol / L potassium persulfate aqueous solution is introduced into the reactor at the same time, and the mass ratio of the amount to the blade block is 1L / kg; after 50 minutes of reaction, the solid product produced by the reaction is taken out of the reactor, and after cooling, a glass fiber with a clean surface and a carbon content of 0.8% is obtained. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this embodiment is 98.1% of the original fiber.

[0062] Comparative Example 1

[0063] First, the retired fan blades were mechanically cut into 30cm×30cm×10cm blade blocks; the pyrolysis reactor was heated to 550℃ and purged with nitrogen; then the cut blade blocks were quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; nitrogen was continuously introduced during the pyrolysis process without using any pyrolysis promoter; after 60 minutes of reaction, the solid product produced by the reaction was taken out of the reactor, and after cooling, a glass fiber with obvious residual pyrolysis carbon on the surface was obtained, with a carbon content of 5.7%. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this comparative example was 59.4% of the original fiber.

[0064] It can be seen from this comparative example that if no pyrolysis promoter is used, a large amount of pyrolytic carbon will remain on the surface of the recycled regenerated glass fiber, and the tensile strength of the regenerated glass fiber is far lower than that of the original glass fiber, making it difficult to reuse as a reinforcing material.

[0065] Comparative Example 2

[0066] First, the retired fan blades were mechanically cut into 30cm×30cm×10cm blade blocks; the pyrolysis reactor was heated to 550℃ and purged with nitrogen; then the cut blade blocks were quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; nitrogen was continuously introduced during the pyrolysis process, and carbon dioxide was introduced into the reactor at a mass ratio of 1.5L / kg to the blade blocks; after 60 minutes of reaction, the solid product produced by the reaction was taken out of the reactor, and after cooling, a glass fiber with obvious residual pyrolysis carbon on the surface was obtained, with a carbon content of 4.1%. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this comparative example was 55.8% of the original fiber.

[0067] From this comparative example, it can be seen that carbon dioxide can react with pyrolytic carbon to a certain extent, but it cannot release H·, OH·, and SO4 under leaf pyrolysis conditions. - · etc., which have strong oxidizing ability, cannot play the role of the pyrolysis promoting agent selected in the present invention, and therefore cannot significantly reduce the pyrolytic carbon content remaining on the surface of the regenerated glass fiber after pyrolysis, and will further have an adverse effect on the tensile strength of the regenerated glass fiber.

[0068] Comparative Example 3

[0069] First, the retired fan blades were mechanically cut into 50cm×30cm×20cm blade blocks; the pyrolysis reactor was heated to 550℃ and purged with argon; then the cut blade blocks were quickly placed in a high-temperature pyrolysis reactor for pyrolysis reaction; during the pyrolysis process, argon was continuously introduced, and a 9mol / L sodium sulfate aqueous solution was introduced into the reactor at a mass ratio of 1.5L / kg to the blade block; after 40 minutes of reaction, the solid product produced by the reaction was taken out of the reactor, and after cooling, a glass fiber with obvious residual pyrolytic carbon on the surface was obtained, with a carbon content of 5.4%. Through the fiber tensile test, the tensile strength of the regenerated glass fiber obtained in this comparative example was 61.2% of the original fiber.

[0070] This comparative example shows that under the conditions of leaf pyrolysis, sodium sulfate cannot generate SO4 with strong oxidizing ability. - The free radicals cannot completely decompose the resin matrix in the retired fan blades, and the pyrolysis promoting agent selected in the present invention cannot play a role, so it cannot effectively reduce the pyrolytic carbon content remaining on the surface of the regenerated glass fiber after pyrolysis, and cannot improve the tensile strength of the regenerated glass fiber.

[0071] Table 1 lists the relevant process parameters in each embodiment and comparative example, as well as the carbon content and tensile strength retention rate of the regenerated glass fiber. The carbon content of the regenerated glass fiber is less than 1%, and the tensile strength retention rate is above 97%, which proves that the method for pyrolyzing and recovering clean glass fiber from retired fan blades proposed in the present invention has an excellent recovery effect.

[0072] Table 1 Process parameters in the embodiments and comparative examples and carbon content and strength retention rate of the regenerated glass fibers

[0073]

[0074]

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for pyrolyzing and recovering glass fibers from retired wind turbine blades, characterized in that: The following steps are involved: (1) After removing the metal components from the retired wind turbine blades, cut them into blade blocks; (2) placing the blade block obtained in step (1) and a pyrolysis promoter in a pyrolysis reactor, and performing a pyrolysis reaction under an inert atmosphere, wherein the pyrolysis reaction temperature is 400-600°C, and the pyrolysis reaction time is 30-60 min; wherein the pyrolysis promoter is selected from one of an aqueous solution of acetic acid, an aqueous solution of hydrogen peroxide, an aqueous solution of an organic alcohol, and an aqueous solution of a persulfate; wherein the concentration of the pyrolysis promoter is 5-10 mol / L, and the ratio of the amount thereof to the mass of the blade block is 1-1.5 L / kg; the pyrolysis promoter is capable of generating active free radicals with strong oxidizing ability at high temperatures, wherein the active free radicals effectively collide with polymer macromolecular chains, so that the resin matrix can be fully combined with the free radicals to form short-chain small molecule products during the cracking process of the resin matrix, thereby inhibiting the secondary polymerization of the polymer cracking products and the generation of pyrolytic carbon, thereby promoting the complete cracking of the resin matrix in the retired fan blade, and thereby realizing the in-situ removal of the organic pyrolytic carbon remaining on the fiber surface after the cracking of the resin matrix under a reducing atmosphere; (3) After the reaction, the solid product is taken out from the pyrolysis reactor and cooled to obtain regenerated glass fiber; the carbon content of the regenerated glass fiber is less than 1%, and the tensile strength retention rate of the regenerated glass fiber is more than 97%.

2. The method according to claim 1, characterized in that In step (1), the size of the blade block is 30~100 cm×20~50 cm×10~20 cm.

3. The method according to claim 1, characterized in that In step (2), the inert atmosphere for the pyrolysis reaction is a nitrogen or argon atmosphere.

4. The method according to claim 1, characterized in that: In step (2), the organic alcohol is selected from one of isopropanol, n-butanol and ethylene glycol.

5. The method according to claim 1, characterized in that In step (2), the persulfate is selected from one of sodium persulfate, potassium persulfate and potassium hydrogen persulfate.

6. A regenerated glass fiber, characterized in that: The regenerated glass fiber is obtained by the method for pyrolyzing and recovering glass fiber from retired wind turbine blades as described in any one of claims 1 to 5, wherein the carbon content of the regenerated glass fiber is less than 1%, and the tensile strength retention rate of the regenerated glass fiber is above 97%.

Citation Information

Patent Citations

  • Waste wind power blade recovery method

    CN112024583A

  • Waste fan blade pyrolysis recovery system and working method thereof

    CN113046107A

  • Waste wind power blade microwave cracking treatment system and method based on coal-fired power plant

    CN113278438A

  • High-temperature nitrogen pyrolysis treatment and recovery method for retired fan blades

    CN114656985A

  • Oriented depolymerization recovery method for retired fan blade

    CN114634653A